(untitled) - Curtis, Paul D. (Clifton Park, NY, 2008)
This practical "how-to" training manual focuses on the best practices for wildlife control, the prevention of wildlife damage problems and realistic assessment of job risks for wildlife control operators. It is currently the only comprehensive manual that offers a step-by-step approach to the practical application of the theory of integrated wildlife damage management. This manual gives professionals the tools they will need to think critically and creatively, so they can choose successful solutions for the many different situations they will encounter in their work. The manual describes a broad array of tools, techniques, and resources backed by an easily understood decision-making model. The basic biology and natural history of the species most likely to cause nuisance problems, with specific management recommendations for each species is included. The safety, ethical, and legal issues related to wildlife control activities is also included
Keywords: Wildlife pests,Động vật hoang dã; Control,Kiểm soát